An insight into the retrogradation behaviors and molecular structures of lotus seed starch-hydrocolloid blends. (15th October 2019) - Zheng, Mingjing; Su, Han; You, Qingxiang; Zeng, Shaoxiao; Zheng, Baodong; Zhang, Yi; Zeng, Hongliang
Highlights: LS retrogradation following autoclaving increased by CS and decreased by GG or XN. CS increased ordered structure, leached amylose and decreased Mw in LS-CS system. Enwrapping effect of GG or XN on LS lowered granule swelling and amylose leaching. The altered structures induced different retrogradation of LS-hydrocolloid blends. Abstract: The retrogradation behaviors and molecular structures of lotus seed starch (LS) combined with different hydrocolloids, chitosan (CS), guar gum (GG) and xanthan (XN), were investigated. Following an autoclave treatment, the storage modulus ( G' ) value of LS-CS increased more rapidly than LS alone, indicating an increase in starch retrogradation. This might result from intermolecular interactions, increased ordered structure, decreased weight-average molecular weight ( Mw ) and greater leached amylose content in LS-CS system. The LS-GG and particularly LS-XN blends showed the opposite trend. The much greater Mw of LS-XN was mainly attributed to the lower retrogradation rate. The enwrapping effect of GG or XN on LS, as observed by confocal laser scanning microscopy, might retard their retrogradation by limiting the granules' swelling and the amylose leaching. Overall, the changes in the interaction force, ordered structure, Mw, leached amylose and microstructure were related to retrogradation behaviors of LS-hydrocolloid blends following an autoclave treatment.